The written language in preschool: a socio constructivist proposal with support of computer resources - Luna Martínez, María Teresa (2019)
This article presents the results of a research completed in 2016, with nine girls and six preschool children from a private institution in the city of Bucaramanga, Colombia. The objective was to show the progress of his writing process in a socio-constructivist environment with the use of computer resources. It was executed under the qualitative approach, with research-action design and non-participant observation. Four workshops on the subject of living and non-living beings were presented, emphasis was placed on collaborative work with the support of computer resources, writing activities with paper and pencil, and on the computer, with the use of the keyboard. The resulting evidences were classified according to the levels proposed by Emilia Ferreiro: pre-syllabic, syllabic, syllabic-alphabetic and alphabetical. Likewise, the texts produced by the student body were compared in the two modalities, and it was observed that, at the end of the process, six students, in total, were located at the alphabetical level in pencil and paper mode, while with the use of the keyboard two. Apparently, the latter was due to several having their first contact with the computer in the field work. These results show, in addition, the need for a preschool aimed at the use of computer resources and a didactic aimed at play, culture and socialization as a literacy excuse, and designed, in such a way, that children constitute the center of literacy.